2000
DOI: 10.1038/sj.ejcn.1600972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blueberry and cranberry juice consumption on the plasma antioxidant capacity of healthy female volunteers

Abstract: Objective: To assess whether consumption of 500 ml of blueberry juice or cranberry juice by healthy female subjects increased plasma phenolic content and antioxidant capacity. Design: Latin square arrangement to eliminate ordering effects. After an overnight fast, nine volunteers consumed 500 ml of blueberry juice, cranberry juice or a sucrose solution (control); each volunteer participated on three occasions one week apart, consuming one of the beverages each time. Blood samples were obtained by venipuncture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 26 publications
(27 reference statements)
2
93
1
Order By: Relevance
“…The increase in plasma ascorbic acid concentration after test juice consumption was small compared with other studies where significant effects on antioxidant capacity were reported (Cao et al, 1998;Pedersen et al, 2000;Samman et al, 2003;Volkovova et al, 2005).…”
Section: Discussionmentioning
confidence: 56%
“…The increase in plasma ascorbic acid concentration after test juice consumption was small compared with other studies where significant effects on antioxidant capacity were reported (Cao et al, 1998;Pedersen et al, 2000;Samman et al, 2003;Volkovova et al, 2005).…”
Section: Discussionmentioning
confidence: 56%
“…Fruit contained high levels of vitamins, minerals, fiber and other antioxidants, and eating fruits increased the concentration of the elements in plasma (Broekmans et al, 2000). Additionally, fruit juice could inhibit the genotoxicity and endogenous formation of N-nitroso compounds (Ohsawa et al, 2003), and increase the plasma capacity of antioxidation (Pedersen et al, 2000). Ascorbic acid (vitamin C) was reported to protect the nitrosame-induced cytotoxcity, genotoxicity and DNA damage in human hepatoma cell line (Arranz et al, 2007;Erkekoglu and Baydar, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant capacity of plasma was estimated by its ability to donate a hydrogen atom or electron to the synthetic free radical, potassium nitrosodisulphonate (Fremy's salt) detected by electron spin resonance (ESR) spectroscopy [18]. In brief, 50 l of a 10-fold dilution of plasma was mixed with an equal volume of Fremy's salt [0.05 mM in 10 ml phosphatebuffered saline(PBS)] and the spectrum of the low field resonance of the Fremy's radical was recorded after 5 min.…”
Section: Biochemical Analysismentioning
confidence: 99%